Karyotype Analysis of Five Bellevalia Lapeyr. Species (Asparagaceae) from Turkey - Eroglu, Huseyin; Pinar, Suleyman Mesut; Dogan, Gulden; Paksoy, M. Yavuz; Kiran, Yasar (Univ Tokyo Cytologia, 2022)
The chromosome numbers and karyotypes of five species of the genus Bellevalia distributed in Turkey were analyzed. These taxa are B. anatolica B. Mathew & Ozhatay, B. fominii Woronow, B. kurdistanica Feinbrun, B. rixii Wendelbo, B. turcica Pinar & Eroglu. Three of them (B. anatolica, B. rixii and B. turcica) are endemic in Turkey. The chromosome numbers of all studied taxa were determeined as 2n=2x= 8. Haploid chromosome lengths varied from 57.78 mu m (B. fominii) to 68.17 mu m (B. anatolica) among species. Karyotype analysis showed that Bellevalia taxa generally have median (m), submedian (sm), and subterminal (st) chromo-somes, but not subterminal chromosomes in B. fominii species.
Keywords: Asparagaceae; Bellevalia; Chromosome number; Karyotype; Turkey